Learning to direct attention: Consequences for procedural task training programs - Monique D. Crouse (Acta Psychologica)
Procedural training programs such as augmented and virtual reality programs often present cues that direct trainees' attention to particular locations and/or items to facilitate learning. However, the impact of different types of cues on trainees' learning is poorly understood. For example, cues that indicate the location of to-be-pressed buttons might cause a trainee to focus on button locations rather than their icons. If the trainee later needs to use a differently-arranged interface, they may be unable to complete the tasks and may need retraining. The current study trained people with either location cues or icon cues and then had them perform the same tasks with a rearranged layout. The results indicate that what a trainee learns is impacted by the type of cue and the type of icons in the interface. When the interface contained icons that represented their function, participants trained with location cues had poorer accuracy and reported experiencing higher difficulty using the interface than participants trained with icon cues, suggesting that icon cues may lead to greater learning than location cues. Both groups, though, maintained similar accuracy when the interface rearranged, indicating they both learned button icons. When the interface contained abstract icons, participants trained with icon cues were able to maintain higher accuracy with the rearranged interface compared to participants trained with location cues suggesting they had greater knowledge of button icons. This finding indicates designers of procedural training programs should consider how cue type could impact a trainee's learning, particularly with abstract icons.